Lignin-based polyurethane materials - Cateto, Carolina (2008)
Four technical lignins (Alcell, Indulin AT, Sarkanda and Curan 27-11P) were used as macromonomers in the synthesis of polyurethane materials following two global approaches. In the first one Alcell and Indulin AT lignins were used directly as co-monomers in combination with a linear polycaprolactone (PCL) in order to produce polyurethane elastomers where lignin content varied between 10 and 25% (w/w) with respect to polyol mixture (PCL+lignin). The thermomechanical properties of the resulting materials were determined by dynamical mechanical analysis (DMA), differential scanning calorimetry (DSC) and swelling tests. In lignin-based elastomers Indulin AT showed to be more efficiently incorporated in the polyurethane network compared with Alcell lignin. Elastomers prepared with Indulin AT lignin exhibited a cross-linking density and storage modulus (rubbery plateau) higher than those of Alcell lignin-based counterpart and a lower soluble fraction. For both Alcell and Indulin AT based elastomers the glass transition temperature increased and extended over a wide temperature range with the increase of lignin content. The second approach consisted of producing rigid polyurethane foams (RPU) using ligninbased polyols obtained after chemical modification by an oxypropylation procedure. Two polyol formulations (20/80 and 30/70, in what concerns the weight ratios between lignin and propylene oxide, PO), were used in RPU formulations and their content varied from 0 to 100% (w/w with respect to a commercial polyol, used as a reference). The resulting RPU foams were characterized in terms of density, mechanical properties, conductivity and morphology. The prepared RPU foams with lignin-based polyols presented properties, very similar to those obtained from conventional commercial polyols. RPU foams prepared with 30/70 polyols exhibited improved properties comparatively to those arising from 20/80 formulations. Exceptions were however detected in RPU foams prepared with all Sarkanda lignin based polyols and Curan 27-11P 30/70 formulation, which were found to be inadequate for RPU formulation.